Orientações de alta: cartões padronizados ajudam na compreensão dos pacientes do pronto socorro? - Reis, Phillipe Geraldo Teixeira De Abreu [UNESP]; Nakakogue, Camila; Nakakogue, Tabatha; Nasr, Adonis; Tomasich, Flávio Daniel Saavedra; Collaço, Iwan Augusto (Colégio Brasileiro de Cirurgiões, 2013)
OBJECTIVE: To determine whether the addition of discharge standard illustrated cards improves understanding of patients in the emergency room. METHODS: We conducted a prospective, randomized, interventional study with 228 patients discharged from the emergency department. All patients were interviewed and tested for the level of understanding of discharge instructions. Some of them received the intervention, with the standard cards, and another did not, constituting the control group. RESULTS: The average of followed discharge guidelines of the group that received the cards was higher than the control group, with statistical significance (p=0.009). When segregated by age, the group between 16 and 35 years of both sexes had the best average of followed guidelines, statistically, than the average of the control group (p=0.01). The difference between the mean orientations between the control group and the card for patients undergoing procedures was statistically significant (p=0.02); as for the stratification according to the number of procedures, the significance increases when that is equal to 1 (p=0.001) and decreased the more procedures were carried out. CONCLUSION: The introduction of discharge standard orientation cards was associated with improvement in the understanding of patients. Without replacing the verbal directions, which establishes dialogue and doctor-patient bonding, cards appear as auxiliary elements, facilitating understanding and care guidelines.

OBJETIVO: determinar se a adição de cartões padronizados de alta ilustrados melhora a compreensão dos pacientes do pronto socorro. MÉTODOS: estudo prospectivo, randomizado e intervencionista com uma amostra de 228 pacientes que receberam alta do pronto socorro. Todos os pacientes foram entrevistados e testados quanto ao grau de compreensão das orientações de alta, sendo que uma parte havia recebido a intervenção com cartões padronizados e outra não, constituindo o grupo controle. RESULTADOS: a média de orientações domiciliares do grupo que recebeu o cartão de alta foi superior ao do grupo controle, com significância estatística de p=0,009. Se fracionado tal dado segundo faixas etárias, aquela compreendida entre 16 e 35 anos, para ambos os sexos, foi a qual a média de orientações do grupo com o cartão é melhor, estatisticamente, do que a média do grupo controle (p=0,01). A diferença entre as médias de orientações entre o grupo controle e o cartão para os pacientes submetidos a procedimentos foi significativa estatisticamente (p= 0,02) e em uma estratificação segundo o número de procedimentos, a significância aumenta quando aquele é igual a 1 (p=0,001) e diminui quanto mais procedimentos são realizados. CONCLUSÃO: A instituição de cartões de alta padronizados foi associada com a melhoria na compreensão dos pacientes. Sem substituir as orientações verbais, que estabelecem o diálogo e a aproximação médico-paciente, os cartões figuram como elementos auxiliares, facilitando as orientações e entendimento do cuidado.
Guidelines for discharge: do standardized cards help in patient understanding?
Keywords: Pacientes; Ferimentos e lesões; Serviços médicos de emergência; Compreensão; Alta do paciente; Patients; Wounds and injuries; Emergency medical services; Comprehension; Patient discharge